Reformasi Birokrasi Lokal Melalui Pelayanan Terpadu - Zuhro, R. Siti (Jurnal Penelitian Politik, 2008)
During the transition period, societal forces participated much more in the formation of policy. This suggests that the real and significant role ofsocietal forces and the strengthening of the political participation of the people has become crucial in contemporary Indonesia. Decentralization and regional autonomy would be hard to realize without the local buraeucracy being reformed. Thus, the establishment of best practices in some regions in Indonesia shows clearly that as a mater of fact, although the benefit of decentralization has not been substantively felt by most regions, some regions have been capable of making positive breakthroughs in the form of improvement of their public services either in the education sector or in healthcare like what has happened in Jembrana Regency (Bali) or services to attract investment like what the Sidoarjo Regency (East Java), Gianyar (Bali), and Tarakan (East Kalimantan) have shown.